Self-harm in mental disorders - Ogłodek, Ewa (Nursing Problems / Problemy Pielęgniarstwa, 2012)
Self-harm that are an expression of self-destruction, are a way of causing pain and damage to the body without an act of suicide. Self-harm in people’s lives fulfill different functions: control your emotions, communication with others, subconscious escape from painful feelings. Particular importance is the therapist’s subjective reaction to make self-harm by the patient, including understanding and reducing the negative aspects of countertransference. Aim of this study is to demonstrate the etiology of self-harm and treatment options. The paper presents the role of traumatic experiences of childhood and adult life. Treatment of self-harm leading to accelerating the process of recovery and improve the social functioning of the patient. It is important that eliminated acts of self-harm and save from suicide. To achieve the desired therapeutic effect are needed therapeutic methods effective for an individual patient.